Arrhythmogenic Right Ventricular Dysplasia (ARVD) Diagnosis In The Elderly - Arunakul, Ing-orn; Chaothawee, Lertlak; Suchato, Chirochana (The Bangkok Medical Journal, 2012)
Arrhythmogenic right ventricular dysplasia (ARVD) is a type of nonischemic cardiomyopathy which primarily involves the right ventricle (RV). ARVD is considered a major cause of sudden death in young adults, mainly in the age group under thirty years old and is rarely found in the elderly. Males are predominantly affected.1-3 ARVD has been proposed as a genetic inherited disease with autosomal dominant and various penetrance patterns.4, 5 ARVD is pathologically characterized by fibro-fatty or fatty replacement of the right ventricular myocardial tissue. The fatty form is presented by almost complete replacement without endocardial thinning and found almost exclusively on the RV myocardium. The fibro-fatty replacement is defined as a fatty replacement with endocardial thinning less than 3 mm thickness6.